Effectivity of Haruan (Channa Striata) Extract to Total of Neutrophil in Wistar Traumatic Ulcer Healing of Rattus Novergicus Strain Wistar - Farhana Nur Fadhila; Isidora Karsini S; Nafi’ah (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2018)
Background: Channa striata contains important compounds in the process of tissue synthesis and important role in wound healing, such as albumin, zinc (Zn), copper (Cu), iron (Fe) and unsaturated fat acids. Purpose : To determine the effect of Channa striata extract to the amount of neutrophil in healing process of traumatic ulcer. Material and Method : The design of this study used randomized post test only control group design. 18 wistar rats were divided into 6 groups, i.e: K-1 (no treatment for 1 day), K-3 (no treatment for 3 days), K+1 (giving hyaluronic acid 0.2% for 1 day), K+3 (giving hyaluronic acis 0.2% for 3 days), P1 (giving Channa striata extract 100% for 1 day), P3 (giving Channa striata extract 100% for 3 days). Results : There was a decrease in the number of neutrophil in the treatment group. The mean and standart deviation of the number of neutrophil in the K-1 group (75,96±3,65), K-3 (50,76±2,04), K+1(72,96±2,97),K+3(45,06±2,83),P1(54,20±1,31),P3(32,50±,85). Conclusion : The using of Channa striata extract 100% for 3 days are the most effective in decreasing the amount of neutrophil in healing process of traumatic ulcer of Rattus Novergicus Strain Wistar.